Catalytic Isolation and Physicochemical Properties of Nanocrystalline Cellulose (NCC) using HCl-FeCl3 System Combined with Ultrasonication - Hamid, Sharifah Bee Abd; Chowdhury, Z.Z.; Karim, M.Z.; Ali, M.E. (North Carolina State University, 2016)
This research emphasizes the isolation of nanocrystalline cellulose (NCC) from palm tree cellulose (PTC) and α-cellulose (AC), using acidic FeCl3-assisted catalytic pretreatment coupled with ultrasonication. The cavitation effect of ultrasonication affects the microstructure of the fibers, ultimately enhancing the crystallinity index of the prepared nanocrystalline cellulose (NCC) sample. In this research, Fourier transform infrared spectroscopy (FTIR) was used to identify the specific functional groups on both types of NCC sample. X-ray diffraction (XRD) analysis demonstrated that the isolated NCC from PTC and AC showed a higher crystallinity index of 73.51% and 89.03%, with diameters of 20 to 70 nm and 15 to 50 nm, respectively. The change in surface morphological features was observed by scanning electron microscopy (SEM), atomic force microscopy (AFM), and transmission electron microscopic (TEM) analysis. It was observed that PTC-based NCC had higher thermal stability than the starting cellulosic sample, whereas NCC isolated from AC showed an opposite trend of reduced thermal stability relative to the raw sample. The results indicated that catalytic acid hydrolysis with ultrasonication was able to yield up to 80.88% and 81.20% of NCC from PTC and AC, respectively, which is comparatively high enough for economic viability of the process.